Academic background, political bids and ideological positions of the proposal for systematization in social work in career training in the city of Rosario (Papeles, 2023)
Within the framework of a research and development project, and as a teaching team of the chair of Socio-historical Foundations of Social Work II, we set out to critically review a particular moment in our own history as a discipline-profession condensed in the proposal of Systematization of the Practice.We understand that this is much more than a mere intervention proposal, being able to find expressions, discussions and positions typical of a time in its arguments.This motivated us to focus our gaze on CELATS, finding there the synthesis of an entire previous journey (1970/80) which allowed the irruption of a social work that challenged and served the popular sectors.In order to account for this, the biographical approach was prioritized since our proposal was based on the need to have stories from social workers who participated in those moments, who would account for processes, decisions, obstacles, imbued with decisions and trajectories. personal stories that enriched these more general processes with their personal history.In short, investigating this intervention proposal in those turbulent years provokes and mobilizes us to deconstruct positions of power, ideologies, and epistemologies around the production of knowledge in social work.
Keywords: Systematization of practice; CeLATS; discipline/profession